The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/pc.24896
|View full text |Cite
|
Sign up to set email alerts
|

Gradually failure simulation and energy absorption characteristics of GFRP composite tubes subjected to axial dynamic impact

Abstract: This study aimed to investigate the energy absorption characteristics of glass fiber cloth‐reinforced epoxy resin (GFRP) composites. The axial dynamic impact test and numerical simulation study on 759/5224 circular tubes were conducted, as well as analyzed and discussed the relevant energy‐absorption parameters and failure morphology. Based on continuum‐damage mechanics, considering the anisotropic constitutive model of composites, the failure criterion including stiffness degradation was embedded into the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Parameters related to failure strains of the constituent phases, namely fiber strands, and matrix, significantly impact the ability of FE simulations to accurately depict deformation and failure mechanisms observed in experimental tests. [17][18][19] The simulations were performed using the explicit nonlinear finite element software LS-DYNA. LS-DYNA, a widely used general-purpose finite element package in industries like automotive and aerospace, is considered the benchmark for crash simulations.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Parameters related to failure strains of the constituent phases, namely fiber strands, and matrix, significantly impact the ability of FE simulations to accurately depict deformation and failure mechanisms observed in experimental tests. [17][18][19] The simulations were performed using the explicit nonlinear finite element software LS-DYNA. LS-DYNA, a widely used general-purpose finite element package in industries like automotive and aerospace, is considered the benchmark for crash simulations.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…In GFRP composites, the matrix is comprised of polyester, vinyl ester, phenolic and epoxy resin. They have attracted attention for their energy-absorbing applications [ 85 , 86 ]. The alkali glass (soda-lime glass) is a commonly available glass fiber that is abbreviated as A-glass.…”
Section: Glass Fiber-reinforced Polymer Compositementioning
confidence: 99%
“…[4][5][6][7] It is worth noting that extensive research has demonstrated that the failure mode of thin-walled structures can be guided using special trigger mechanisms. [8][9][10][11][12] Fiber fracture is the most significant characteristic of composite material failure mechanisms. The failure mode of the fibers changes with the angle when subjected to a constant force, so fiber orientation may affect the energy absorption of thin-walled tubes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies related to CFRP thin‐walled tubes, among which three widely reported thin‐walled failure modes are progressive bending mode, progressive splaying mode, and buckling failure 4–7 . It is worth noting that extensive research has demonstrated that the failure mode of thin‐walled structures can be guided using special trigger mechanisms 8–12 …”
Section: Introductionmentioning
confidence: 99%